Endovascular therapy beyond 24 hours for anterior circulation large vessel occlusion or stenosis in acute ischemic stroke: a retrospective study - Wen, An; Cao, Wen-feng; Zhao, Chao; Wu, Ling-feng; Zhou, Yong-liang; Xiang, Zheng-bing; Rao, Wei; Liu, Shi-min (Frontiers in Neurology, 2023)
Background To assess the clinical and safety outcomes of endovascular treatment (EVT) administered more than 24 h after the onset of symptoms in patients with acute ischemic stroke resulting from anterior circulation large-vessel occlusion or stenosis (AIS-ACLVO/S). Methods We enrolled consecutive AIS-ACLVO/S patients who received EVT in our hospital between January 2019 and February 2022 and divided them into two groups based on the time from AIS onset to EVT: EVT < 24 h group and EVT >24 h group. The successful reperfusion (modified thrombolysis in cerebral infarction, [mTICI] ≥2b), 90-day modified Rankin Scale score (mRS), intracranial hemorrhage (ICH), and symptomatic ICH (sICH), as well as mortality, were analyzed in the two groups of patients. Results A total of 239 patients were included in the study, with 214 patients in the EVT < 24 h group (67.8 ± 0.8 years, 126 males) and 25 patients in the EVT > 24 h group (62.80 ± 2.0 years, 22 males). Both groups were similar in terms of hypertension, diabetes history, responsible vessels, and Alberta stroke program early computed tomography scores (p > 0.05). However, the EVT < 24 h group had significantly higher age, history of atrial fibrillation, proportion of patients receiving intravenous thrombolysis, and NIHSS scores before EVT than the EVT > 24 h group. AIS etiology differed between the groups, with more cases of large artery atherosclerosis in the EVT > 24-h group and more cases of cardioembolism in the EVT < 24-h group. Successful reperfusion (mTICI ≥2b), ICH, and sICH were similar between the groups. The 90-day functional independence rate (mRS ≤ 2) was significantly higher in the EVT > 24-h than in the EVT < 24-h group (80% vs. 39.7%, p < 0.001), while the 90-day mortality rate was lower in the EVT > 24-h group (0% vs. 24.8%, p < 0.001). Conclusion In our study, we found that EVT beyond 24 h of symptom onset in patients selected with multimodal MR screening, was associated with high functional independence rates and low mortality. Larger or randomized studies are needed to confirm these findings.